Evaluation of the pulse pressure index at the peak of exercise before and after cardiac rehabilitation - Amir Hossein Yazdi; Parnian Kazemi; Farzaneh Esna-Ashari; Mehrnaz Olfat; Leila Najmafshar (Publisher: Shahid Beheshti University of Medical Sciences, 2017)
Background and Objectives: As a new supplementary therapeutic option, cardiac rehabilitation (CR) is getting more attention each day. Several studies have proved the positive impact on qualitative criteria but few studies have been done on quantitative criteria.The purpose of the survey in this study is to evaluate the impact of CR on non-invasive estimated maximum cardiac output by Pulse Pressure index (PPI) at the peak of exercise.Methods: This is a nonrandomized prospective cohort study conducted in Hamadan, Iran in 2015.100 eligible patients who underwent coronary artery bypass surgery, based on cardiologist permission and an informed consent, participated in our study. The PPI was measured at the peak of exercise before and after standard CR program.Result: In overall, mean of PPI was not significantly different before and after CR. PPI was noticeably increased in patients younger than 60 years old (p = 0.022). In contrast to hypertensive patients, PPI in non-hypertensive patients increased significantly after CR (p=0.002). PPI considerably increased in non-diabetic patients after CR (p=0.046), but not in diabetic individuals. Other variables had not any significant effect on PPI in response to CR.Conclusion: it is clear that PPI is associated with vascular atherosclerosis, as well as cardiac output; Positive effects of CR diminish in older, diabetic and hypertensive patients with more progressive atherosclerosis.